Public pensions in the national accounts and public finance targets - Oksanen, Heikki; European Commission : Directorate-General for Economic and Financial Affairs (Brussels ; Belgium : European Commission: Directorate-General for Economic and Financial Affairs, 2004)
Preparations are underway to revise national accounting to implement actuarial recording of pension liabilities for corporations and government as an employer. This paper extends this to unfunded public pensions with the help of 'implicit tax' in pension contributions. The clearest advantages of the revision appear in situations where pension liabilities are shifted from the corporate sector to government, and where part of the public pension system is privatised. The proposed revision raises public debt and deficit to new orders of magnitude. The paper provides a framework for setting the debt and deficit targets under both current and proposed definitions.
Economic Papers